Chemical-Mineralogical Characterization of Magnetic Materials from Magnetic Soils of the Southern Espinhaço Mountain Chain and of the Upper Jequitinhonha Valley, State of Minas Gerais, Brazil - Alexandre Christófaro Silva; Solange de Souza; José Domingos Fabris; Maurício Soares Barbosa; Uidemar Morais Barral; Roberto Vial Costa (Revista Brasileira de Ciência do Solo)
ABSTRACT In the Southern Espinhaço Mountain Chain and in the Upper Jequitinhonha Valley, magnetic soils, in different pedogenetic stages, are found to be forming over intrusions of basic lithology. The essential chemical and mineralogical properties of samples from magnetic soil profiles from those two physiographic environments in the state of Minas Gerais, Brazil, are reported. Three of the pedons (Rhodic Kandiustox – RKox, Rhodic Haplustox – RHox, and Typic Argiustoll - TAoll) were identified as being indeed developed over basic rocks; the fourth pedon (Typic Haplustox - THox) is currently forming on an acidic rock. Particle size and routine chemical analyses were performed on samples from all horizons of the four selected soil profiles. For a deeper insight into the dominant mineralogy of each diagnostic soil horizon, the elemental contents, expressed in terms of the corresponding metal cation oxides, namely Fe2O3, Al2O3, and MnO2, were obtained from digesting the whole soil samples with sulfuric acid. A similar chemical analytical procedure was performed for the residual solid extracts obtained from attacking the whole soil materials with mixtures of (i) dithionite - citrate - bicarbonate and (ii) oxalate - oxalic acid. The soil samples were also analyzed by Mössbauer spectroscopy at room temperature (~298 °K) in an attempt to better identify the main magnetic iron oxides. Maghemite (δFe2O3) was found in all samples and magnetite (Fe3O4) was identified only for the sample from the Typic Argiustoll. The pedogenetic loss of silica and consequent accumulation of iron and aluminum oxides along the profile are found to be somehow correlated to the weathering sequence in the soils forming on basic rocks: TAoll < RKox < RHox.